Improving University Students' Mental Health During the COVID-19 Pandemic: Evidence From an Online Counseling Intervention in Italy - Celia, Giovanna; Tessitore, Francesca; Cavicchiolo, Elisa; Girelli, Laura; Limone, Pierpaolo; Cozzolino, Mauro (Frontiers in Psychiatry, 2022)
Background The mental health of university students is significantly affected when faced with public health emergencies and requires specific interventions to help support and prevent any long-lasting effects that the pandemic may have on their mental health status. This study aims to evaluate the impact of an online individual counseling intervention provided by the University of Foggia and carried out during the COVID-19 pandemic on the mental health status of a sample of university students. Methods 32 Italian undergraduate students took part in a one-group pretest-posttest research design. The data was gathered in two times: before the start of the counseling intervention (T1), positive and negative affect, satisfaction with life, global mental distress, anxiety, stress, and future time perspective were collected, at the end of the counseling intervention (T2), the same dimensions were measured. A one-way repeated measures multivariate analysis of variance (MANOVA) was performed, and single Bonferroni-corrected dependent t-tests were conducted on variables showing a significant change over time. Results The results showed that positive affect, subjective well-being, and future time perspective increased significantly after the intervention. In contrast, the participants reported significantly lower levels of negative affect, global mental distress, state and trait anxiety, as well as perceived stress over time. Conclusions The study demonstrates the promising impact of online counseling intervention and its efficient contribution in promoting the well-being of university students. The results contribute to the ongoing debate concerning the psychological impact of the COVID-19 pandemic on young adults, helping professionals develop more efficient clinical and psychological interventions.